Isolation of a Unique Marine Bacterium Capable of Growth on a Wide Variety of Polysaccharides from Macroalgae - Quatrano, Ralph S. (1978)
A unique marine bacterium has been isolated which can be cultured on a variety of polysaccharides and cell wall preparations from red and brown algae.